2020
DOI: 10.1016/j.apr.2020.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Observations of volatile organic and sulfur compounds in ambient air and health risk assessment near a paper mill in rural Idaho, U. S. A.

Abstract: The Lewis-Clark Valley is a rural area that includes the cities of Lewiston, Idaho and Clarkston, Washington and the surrounding areas. The largest industry in the Lewis-Clark Valley is a pulp paper mill located in Lewiston which emits particulate matter and odorous sulfur air pollutants. This study analyzed the Lewis-Clark Valley air composition and seasonal, temporal and spatial variations of volatile organic compounds (VOCs) from 2017 to 2018 to determine potential health risks of the paper mill emissions t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…It can be noticed that the industrial units of PVC, iron and steel, paper, machinery, gas power, sewage plants, and so forth, are situated north of the suburban site (Figure 1). Several studies have reported that BTEX and acetaldehyde are emitted in significant amounts from PVC, paper mills, coal power plants, landfill, and cement industries (Dave et al., 2020; Evans, 2009; Garcia et al., 1992; Liu et al., 2019; Scott et al., 2020; Tong et al., 2015). In addition, the emission from sewage treatment plants can also be a source of toluene, benzene, xylene, acetone, acetaldehyde and methanol (Byliński et al., 2019; Quigley & Corsi, 1995; Yang et al., 2012).…”
Section: Resultsmentioning
confidence: 99%
“…It can be noticed that the industrial units of PVC, iron and steel, paper, machinery, gas power, sewage plants, and so forth, are situated north of the suburban site (Figure 1). Several studies have reported that BTEX and acetaldehyde are emitted in significant amounts from PVC, paper mills, coal power plants, landfill, and cement industries (Dave et al., 2020; Evans, 2009; Garcia et al., 1992; Liu et al., 2019; Scott et al., 2020; Tong et al., 2015). In addition, the emission from sewage treatment plants can also be a source of toluene, benzene, xylene, acetone, acetaldehyde and methanol (Byliński et al., 2019; Quigley & Corsi, 1995; Yang et al., 2012).…”
Section: Resultsmentioning
confidence: 99%
“…After samplin Table 2 summarizes instrumental methods, and more detailed descriptions can be found in Scott et al. ( 2020 ) and Miller et al. ( 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…Automated thermal desorption-gas chromatography-mass spectrometry (ATD-GC-MS) is a powerful analytical technique that allows the identication and quantication of gases at trace levels for applications such as the atmospheric analysis of anthropogenic VOCs, 32,33 metabolomics, [34][35][36] and materials analysis. 37,38 In the e-cigarette aerosol analysis eld, ATD-GC-MS has allowed the determination of gas/particle partitioning constants of e-cigarette ingredients 39 including nicotine in heatnot-burn tobacco vaporizers, 40 as well as the identication of myriad degradation products emitted by both nicotine and cannabis vaporizers.…”
Section: Introductionmentioning
confidence: 99%